The effectiveness of the internal control system of Auto Bavaria Sdn.Bhd. in addressing fraud cases / Norhidayu Mohd Yunos - Mohd Yunos, Norhidayu (2014)
The purpose of this study is to examine the effectiveness of the internal control system of Auto Bavaria in addressing fraud cases. Fraud can be considered as the most concerning problem in business due to its impactful effect to most of the companies in the world. However, if companies unconsciously 'motivate' fraudulent activities, then, this trend would most likely to continue in the future. There are many types of fraud such as employees' fraud, customer fraud, accounting fraud, investment frauds, financial fraud, etc. Fraud is one of the biggest issues to damage a company. Therefore, the responsibility of management plays an important role in detecting and preventing fraud. In this study, the researcher would discuss this issue and others as well in relation to the internal control system procedure that employees' applied in working process. The aim of this study is (i) does Sime Darby Auto Bavaria Sdn. Bhd. have an internal control system; (ii) is Sime Darby Auto Bavaria Sdn.Bhd.is internal control system effective enough in preventing potential fraud cases; (iii) does the employees at Sime Darby Auto Bavaria Sdn.Bhd have the requisite knowledge on the prevention and detection of fraud; (iv) the extent seriousness of fraud cases at Sime .Darby Auto Bavaria Sdn. Bhd. This study is based on the primary data supported with other several fraud cases and relevant information from secondary data. The primary data are to be gathered from a survey of 15 finance executives working in the finance department and 20 clerical staffs working in the administration department. All the information obtained in this research will be disclosed unless if it is identified as confidential information. The secondary data will comprise of 3 selected cases out of 10 cases available in the records kept at the finance department. The remaining 7 cases cannot be accessed since they are considered extremely confidential. This study will be supported by a primary data throughout the year 2014 and secondary data from actual cases which were ranged from the year 2009 until 2014. The issue of fraud will be discussed and criticised in this chapter especially on the factors that motivate the employee to abuse their duty, fraud or steal and customer's fraud.